Was hat ein Bügeleisen mit einer Geschichte des Sports zu tun? Intersektionale Geschichte(n) des Sports im Museum - Veronika Springmann (Österreichische Zeitschrift für Geschichtswissenschaften)
What sport is and what significance sport has for societies or individuals people can be told as a story of spectacular events, ravishing feelings, fascinating or feelings, fascinating or regulated bodies, of emancipation, great successes or successes or failures, as a story of belonging and community or as a story of exclusion.